Disputed Waters: Israel's Responsibility for the Water Shortage in the Occupied Territories - Lein, Yehezkel (Journal for the study of religion, nature and culture, 2000)
Water is the most basic resource for human existence. It is vital for human life itself and for personal health and hygiene. Israel’s citizens, like those of other developed countries, benefit year-round from running water in unlimited quantities to meet their household needs. For Israelis, running tap water is taken for granted.